A novel small-molecule inhibitor of HIV-1 entry - Heredia A; Latinovic OS; Barbault F; de Leeuw EPH (Dove Medical Press, 2015)
Alonso Heredia,1,3 Olga S Latinovic,2,3 Florent Barbault,4 Erik PH de Leeuw3,5 1Department of Medicine, 2Department of Microbiology and Immunology, 3Institute of Human Virology, University of Maryland Baltimore School of Medicine, Baltimore, MD, USA; 4Univ Paris Diderot, Sorbonne Paris Cité, ITODYS, UMRCNRS7086, Paris, France; 5Department of Biochemistry and Molecular Biology, University of Maryland Baltimore School of Medicine, Baltimore, MD, USA Background: Antiretroviral therapy has transformed HIV-1 infection into a managed condition with near-normal life expectancy. However, a significant number of patients remain with limited therapeutic options due to HIV-1 resistance, side effects, or drug costs. Further, it is likely that current drugs will not retain efficacy, due to risks of side effects and transmitted resistance.Results: We describe compound 5660386 (3-ethyl-2-[3-(1,3,3-trimethyl-1,3-dihydro-2H-indol-2-ylidene)-1-propen-1-yl]-1,3-benzothiazol-3-ium) as a novel inhibitor of HIV-1 entry. Compound 5660386 inhibits HIV-1 entry in cell lines and primary cells, binds to HIV-1 envelope protein, and inhibits the interaction of GP120 to CD4. Further, compound 5660386 showed a unique and broad-range activity against primary HIV-1 isolates from different subtypes and geographical areas.Conclusion: Development of small-molecule entry inhibitors of HIV-1 such as 5660386 may lead to novel classes of anti-HIV-1 therapeutics. These inhibitors may be particularly effective against viruses resistant to current antiretroviral drugs and could have potential applications in both treatment and prevention. Keywords: HIV-1, defensin, drug, entry, antiviral therapy, CD4